Quality of Integrated Information System Services Population (Sintren) in the Issuance of Birth Certificates Department of Population and Civil Registration Cirebon Regency - Faturrojab, Muhammad Rizal; Desmario, Fadilla; Zulkarnaen, Iskandar (PT FORMOSA CENDEKIA GLOBAL, 2025)
In implementing this system, there are various problems that must be addressed, one of which is the limited human resources and the suboptimal use of SINTREN at the Population and Civil Registration Office of Cirebon Regency. This study aims to analyze and evaluate the quality of services provided by the Population and Civil Registration Office of Cirebon Regency in the implementation of the Integrated Population Information System (SINTREN) in the process of issuing birth certificates. This study uses a qualitative method with a descriptive approach, where data is collected through interviews, observations, and documentation. The results of the study indicate that SINTREN has great potential to improve the quality of public services in the field of population administration and has been regulated in the regional regulations of Cirebon Regency. However, the reality has not been optimal, as seen from several problems and obstacles. The factors causing the quality of service to be suboptimal are tangibles, reliability, responsiveness, assurance, and empathy. Efforts to optimize the quality of the integrated population information service system of the Cirebon District Population and Civil Registration Office include human resource training, community outreach, and simplification of administrative processes, which are essential for optimizing SINTREN.